2019
DOI: 10.1111/ajt.15112
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial permeability regulates cardiac endothelial cell necroptosis and cardiac allograft rejection

Abstract: Transplantation is invariably associated with programmed cell death including apoptosis and necrosis, resulting in delayed graft function and organ rejection. We have demonstrated the contribution of necroptosis to mouse microvascular endothelial cell (MVEC) death and transplant rejection. Organ injury results in the opening of mitochondrial permeability transition pores (mPTPs), which can trigger apoptotic molecules release that ultimately results in cell death. The effect of mPTPs in the necroptotic pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 52 publications
3
30
0
Order By: Relevance
“…In addition, we found a significant downregulation of the transforming growth factor beta regulator 4 ( TBRG4 ) under rejection conditions, which is known to promote apoptosis in knockdown experiments 36 . Our results are in concordance with those of previously published studies, supporting the idea that transplantation is associated with programmed cell death including apoptosis, resulting in delayed graft function and organ rejection 37‐39 …”
Section: Discussionsupporting
confidence: 91%
“…In addition, we found a significant downregulation of the transforming growth factor beta regulator 4 ( TBRG4 ) under rejection conditions, which is known to promote apoptosis in knockdown experiments 36 . Our results are in concordance with those of previously published studies, supporting the idea that transplantation is associated with programmed cell death including apoptosis, resulting in delayed graft function and organ rejection 37‐39 …”
Section: Discussionsupporting
confidence: 91%
“…Indeed, a recent heart transplant study reported MLKL phosphorylation and necroptosis downstream of PPIF activation. 38 Although dual deficiency of PPIF or MLKL elicited the most potent protective effect on tubular injury, the combinations of two cell death inhibitors with doubtful specificities did not. These data do not exclude independent roles of the both pathways in acute oxalosis, but are consistent with a significant interference of both pathways in crystal cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…62,63 We have shown that increased level of Treg cell in lymphoid organ and in the graft correlated with long-term mouse graft survival posttransplant. 17,[64][65][66][67] Necroptosis results in the release of danger molecules from cells as being demonstrated by us and others. 2,[14][15][16] Danger molecules not only participate in graft rejection, 2 they may also provoke inflammation and block tolerance induction via the inhibition of Treg cells.…”
Section: Discussionmentioning
confidence: 70%
“…In murine transplantation studies, we showed that cells and grafts release HMGB1 under necroptosis. [14][15][16][17] Others have reported that HMGB1 may interact with TLR4 to worsen murine transplant injury or rejection. 5,47,48 However, the roles of other damaging molecules and their receptors in transplant AJT rejection have not been well defined.…”
Section: Discussionmentioning
confidence: 99%